2018
DOI: 10.1021/acs.analchem.8b01740
|View full text |Cite|
|
Sign up to set email alerts
|

Depth-Profiling Microanalysis of CoNCN Water-Oxidation Catalyst Using a λ = 46.9 nm Plasma Laser for Nano-Ionization Mass Spectrometry

Abstract: Nanoscale depth profiling analysis of a CoNCN-coated electrode for water oxidation catalysis was carried out using table-top extreme ultraviolet (XUV) laser ablation time-of-flight mass spectrometry. The self-developed laser operates at λ = 46.9 nm and represents factor of 4 reduction in wavelength with respect to the 193 nm excimer laser. The reduction of the wavelength is an alternative approach to the reduction of the pulse duration, to enhance the ablation characteristics and obtain smaller quasi-nondestru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
10
0
1
Order By: Relevance
“…State-of-the-art laser ablation has, however, a few limitations that may be addressed in the near future, thanks to shorter wavelengths [1,2]. First, the ablation mechanism is associated with thermo-mechanical processes that may modify the material composition, or damage a large portion of it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…State-of-the-art laser ablation has, however, a few limitations that may be addressed in the near future, thanks to shorter wavelengths [1,2]. First, the ablation mechanism is associated with thermo-mechanical processes that may modify the material composition, or damage a large portion of it.…”
Section: Introductionmentioning
confidence: 99%
“…Aim of this work was to compare the performance of traditional visible laser ablation microanalysis with more advanced short-wavelength (XUV) laser ablation, on the case of CZTS functional thin films for PV. Previous studies on water-oxidation catalysis showed a remarkable impact in mapping rapidly the 3D chemical and mechanical modifications of a sample cycled in the electrocatalytic system l [1]. The sample did not lose its functionality, such that it is in principle possible to deploy XUV-MS for real-time operando spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Although agreement between the mass spectra acquired using the 26.5 eV and 10.5 eV lasers was highlighted, it was pointed out that the XUV ionization approach allows all the species in the sample to be measured, that are otherwise inaccessible with the 10.5 eV laser . Our own recent study showed the benefit of XUV depth profiling with TOF for nano‐scale microanalysis of water‐oxidation catalysts …”
Section: Introductionmentioning
confidence: 99%
“…The state-of-the-art short wavelength laser utilized for microanalysis has been for long time the excimer at 193nm [2][3][4][5][6][7] , with the spatial resolution in the large micron range. The cutting down of the laser wavelength is beneficial to (i) enhance the space resolution, (ii) eliminate elemental fractionation by using a high photon energy, (iii) improve the sample utilization efficiency, by efficient coupling as well as negligible plasma shielding.…”
Section: Introductionmentioning
confidence: 99%
“…A seminal paper by Kuznetsov et al 8 demonstrated the capability for nano-scale mass spectrometry (MS). Müller et al 3 showed that this implied a 5 orders of magnitude reduction of sampled mass, which did not turn into an equivalent reduction in MS sensitivity, thus concluding a more efficient sample utilization 9 . The occurrence of fractionation as well as matrix effects is expected to be mitigated compared to ion bombardement techniques, which demands further analysis.…”
Section: Introductionmentioning
confidence: 99%